2021
DOI: 10.14710/jmki.9.1.2021.38-44
|View full text |Cite
|
Sign up to set email alerts
|

Compensation, Job Stress, and Job Satisfaction on Nurse Turnover Intention at Ananda Bekasi Hospital

Abstract: One of the high turnover rates in the hospital occurs in nurses. More attention is needed because turnover can be detrimental to the organization, in terms of cost, resources, and effectiveness of nursing. The research objective is to obtain empirical evidence whether there is an effect of compensation, job stress and job satisfaction on turnover intention at Ananda Bekasi Hospital in 2020. The research method is to use causality design based on the time dimension of one short study. The sample used was satura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…This study confirm the findings that job satisfaction has a negative influence on salespeople turnover intention in the automotive sector. However, there have been previous studies using health workers as research subjects (Amanda et al, 2021). Research has shown when job satisfaction decreases, it will increase employee turnover.…”
Section: Discussionmentioning
confidence: 99%
“…This study confirm the findings that job satisfaction has a negative influence on salespeople turnover intention in the automotive sector. However, there have been previous studies using health workers as research subjects (Amanda et al, 2021). Research has shown when job satisfaction decreases, it will increase employee turnover.…”
Section: Discussionmentioning
confidence: 99%
“…Yousuf and Saqib (2021) also presented the same results but complemented them by showing that employees with disabilities were offered lower job satisfaction than non-disabled workers. In addition, job satisfaction had identified as the main reason employees leave their jobs (Amanda et al, 2021;Faizah et al, 2021). Employees' job satisfaction and turnover intention in the banking sector of Nigeria (Otache & Inekwe, 2021;Mulyawan et al, 2021).…”
Section: Job Satisfactionmentioning
confidence: 99%
“…This finding demonstrates a positive connection between job stress and employee turnover. Unreliable workplaces affect employee job security leading to poor job satisfaction and promoting anxiety and turnover intentions (Choi & Kim, 2020;Amanda et al, 2021;. Countless previous scholars claimed that the more significant the amount of stress, the greater the employee's turnover intention increases (Yukongdi & Shrestha, 2020;.…”
Section: Job Stressmentioning
confidence: 99%
“…In addition, related to employee job satisfaction, there are two concepts that are currently receiving attention from researchers in the fields of organizational behavior and human resource management, namely quality of work-life and work-life balance (Aruldoss et al, 2020). Several other variables related to the importance of quality of work-life, work-life balance and employee job satisfaction are job commitment and job stress (Amanda et al, 2021;Aruldoss et al, 2020;Batugal & Tindowen, 2019;Wardana et al, 2020).…”
Section: Introductionmentioning
confidence: 99%